The role of Tállya’s andesite quarry in the landscape and landscape pattern - Módosné Bugyi, Ildikó; Csima, Péter (4D Journal of Landscape Architecture and Garden Art, 2025)
The country's most significant active andesite quarry is located within a World Heritage site and designated as a historic landscape, which is also very important for tourism. A landscape pattern analysis and visual assessment were conducted before the recently completed landscape rehabilitation of the waste rock dumps surrounding the quarry. This study presents the research that formed the basis for planning and highlights the need for historical landscape investigations and visual analysis. We developed a unique, empirical method for conducting the visual analysis of waste rock dumps, though the methodology description is not part of this study. The paper also illustrates the importance of rehabilitating areas damaged by mining activities.
Keywords: andesite quarry; Tállya; waste rock dump; fit into the landscape; landscape rehabilitation